PENGEMBANGAN E-MODUL PADA MATERI SISTEM KOMPUTASI PADA MATA PELAJARAN INFORMATIKA KELAS X DKV DI SMK NEGERI 4 PADANG - Desril, Nofil; Alfiriani, Adlia; Novita, Rini (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research was carried out based on problems, namely that students did not have complete printed modules personally, teachers still used conventional methods, there was no E-Module to support the Informatics learning process at SMK Negeri 4 Padang. The aim of this research is to develop an E-Module. The research method used is the Research and Development (RD) method with the ADDIE development model. The subjects of this research were 25 students as samples. The data collection technique uses a questionnaire with a Likert scale. At the testing stage, Alpha testing is used, namely media expert validity testing and material expert validity testing, as well as Beta testing, namely teacher practicality testing and student practicality testing. The results of the research show that the validity level of the E-module obtained a score of 89.5% in the very valid category, the teacher's practicality level obtained a score of 98% in the very practical category and students' practicality obtained a score of 83.3% in the very practical category. Based on this data, it can be concluded that this E-Module is suitable for use in the learning process. The results of this research are recommended for informatics subject teachers in the DKV class at SMK Negeri 4 Padang.